Carbon Emission Reduction and Financial Performance in an Emerging Market: Empirical Study of Indian Firms - Leo Themjung Makan; Kailash Chandra Kabra (Indonesian Journal of Sustainability Accounting and Management, 2021)
The study aims to examine the impact of carbon emission reduction on financial performance in an emerging market context. Thirty eight Indian-listed firms were drawn from the Bombay Stock Exchange for the sample, and firms' data were collected from sustainability reports and Capitaline Plus corporate database. Carbon productivity and market-to-book ratio were used as a proxy to measure carbon emission reduction and financial performance, respectively. Results show a positive association between carbon emission reduction and financial performance after employing the appropriate panel regression model. This study contributes to the ongoing “pays to be green” literature, and the findings of this study complement the “win–win” research by empirically showing that corporate effort to reduce carbon emission generates a positive impact on firm's financial performance. Moreover, the findings provide crucial managerial and policy implication.